PERLINDUNGAN HUKUM BANGUNAN CAGAR BUDAYA DI KOTA MALANG SEBAGAI WARISAN BUDAYA BANGSA - Sulthon Miladiyanto; Ririen Ambarsari; Anindya Bidasari (Jurnal Analisis Hukum, 2018)
Cultural heritage is a nation's assets that have very valuable values, in which they are able to tell many historical events of the struggle as learning material to build the nation's character and have high artistic values that are able to inspire and have economic value for the prosperity of society. Therefore, it needs a planned and systematic effort to provide protection to cultural heritage. The constitution is the basis for the legislation promulgated by both central and regional governments including Law Number 11 of 2010 concerning Cultural Heritage, East Java Governor Regulation Number 66 of 2015 concerning Preservation of Cultural Heritage in East Java Province, and Malang City Regulation Number 1 of 2018 concerning Cultural Heritage and other relevant laws and regulations. Malang City Government through several businesses that retain historical heritage buildings: 1) Utilization of the utilization of Cultural Heritage for the benefit of the people's welfare while maintaining its sustainability, 2) Revitalization is a development activity aimed at regrowing the important values of Cultural Heritage by adjusting the function of a new space that is not in conflict with the principles of preservation and cultural values of the community, and 3) Adaptation is an effort to develop a Cultural Heritage for activities that are more in line with the needs of the present by making limited changes that will not result in deterioration in its importance or damage to parts that have important value.